2012
DOI: 10.1021/ef3012849
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Renewable and Synthetic Diesel Fuel Blendstocks: Composition and Properties

Abstract: We examined the chemical composition and properties of several diesel fuels and blendstocks derived from Fischer–Tropsch (FT) synthesis, hydroisomerization of lipids, and fermentation of sugar via the terpenoid metabolic pathway. Comprehensive two-dimensional gas chromatographic analysis with nonpolar and polar columns, 13C NMR, GC-MS, and elemental analysis were used to assess fuel chemistry. Performance properties included density, heat of combustion, cetane number, and cloud point, as well as other properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 13 publications
4
68
0
Order By: Relevance
“…Smagala et al [217] examined the effect of the isomerization on the CN number and the cloud point and shown that an initial mixture of normal saturation hydrocarbons with a CN rating of about 118 and a cloud point of 20 • C can be converted into a practical green diesel fuel of a cloud point down to −30 • C while keeping the CN number above 70. Another property which indicates the low temperature operability of the diesel fuel is the Cold Filter Plugging Point (CFPP).…”
Section: Green Diesel Propertiesmentioning
confidence: 99%
“…Smagala et al [217] examined the effect of the isomerization on the CN number and the cloud point and shown that an initial mixture of normal saturation hydrocarbons with a CN rating of about 118 and a cloud point of 20 • C can be converted into a practical green diesel fuel of a cloud point down to −30 • C while keeping the CN number above 70. Another property which indicates the low temperature operability of the diesel fuel is the Cold Filter Plugging Point (CFPP).…”
Section: Green Diesel Propertiesmentioning
confidence: 99%
“…[6] Until recently, the U.S. underground mining industry has been almost exclusively using biodiesel fuels made from various vegetable oils and animal fats through the process of transesterification. [7] Those fuels are made of long-chain, fatty-acid methyl esters (FAME). FAME biodiesels are oxygenated fuels with approximately 11% oxygen content.…”
Section: Introductionmentioning
confidence: 99%
“…[27] HVORD is almost exclusively made of paraffinic and iso-paraffinic hydrocarbons and is virtually free of aromatic hydrocarbons, metals, sulfur, nitrogen, and oxygen-containing compounds. [7,26,27] When compared with ULSD, HVORD fuels have a lower density, a higher cetane number, higher net heat of combustion on a mass basis, and lower net heat of combustion on a volume basis. [26] …”
Section: Introductionmentioning
confidence: 99%
“…FAME biodiesels contain on average between 10 and 11 percent oxygen. HVORD fuels are made from vegetable and algae oils and animal fats through hydrogenation and isomerization processes (Huber, O’Connor and Corma, 2007; Aatola et al, 2008; Smagala et al, 2013). By chemical composition, HVORD consists of mixtures of paraffinic and isoparaffinic hydrocarbons and is virtually free of aromatic hydrocarbons, metals, sulfur, nitrogen and oxygen-containing compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Due to technical issues with high-pressure injection systems in the new-technology diesel engines, the majority of engine manufacturers only support the use of blends with low FAME-biodiesel content. The main restriction of HVORD was found to be compatibility with some materials (Smagala et al, 2013), lubricity and cold flow properties (Lapuerta et al, 2011). …”
Section: Introductionmentioning
confidence: 99%